Pendekatan Pembelajaran yang Menggunakan Kearifan Lokal sebagai Sumber Utama dalam Mengajarkan Materi IPS di Sekolah Dasar - Wardaturohmah; Dwi Oktaviani; Navissa Amelia Revalina; Sri Enggar Kencana Dewi; Luli Rusmala Dewi; Selpiyani Selpiyani (Lembaga Pengembangan Kinerja Dosen, 2026)
This research has a crucial objective to facilitate primary school (SD) teachers so they are able to effectively and efficiently integrate and present Social Studies (IPS) material enriched with the content of local wisdom. Local wisdom is defined as a treasure inherited through generations, encompassing in-depth knowledge, real practices, and fundamental values that have developed and been firmly held within the local community. This foundation makes the learning process not only informative but also highly relevant and meaningful for students’ lives. This article specifically highlights that the integration of values, culture, and knowledge sourced from the local area can produce significant positive impacts. These impacts include improving students' conceptual understanding of Social Studies material, fostering their active participation in the classroom, and honing essential critical thinking skills. Teachers are encouraged to use a contextual approach or a real-life-based approach, so the material taught feels close to the students' experiences and is easier to grasp. The values embedded in local wisdom will function as a strong bridge in understanding every material concept. Thus, the knowledge acquired by students does not only stop at the cognitive level (merely theoretical knowledge), but can also be implemented concretely in the form of real actions and behavior outside the school environment. This local wisdom-based learning approach will ultimately become an important connection that guides students to act appropriately, ethically, and solution-oriented in responding to various problems they face in their daily lives.